Urbane Wirtschaftsdynamik und ethnischer Dualismus. Dargestellt am Beispiel der Stadt Bozen - Achenbach, Hermann (ERDKUNDE, 1974)
The city of Bolzano, centre of the Italian alpine province of the same name (South Tyrol) exemplifies the linkages between urban economic development and an ethnically dualistic situation. Although many changes have been arbitrarily set in train by politics and the free play of competitive forces is strongly constrained, a number of changing structural influences can be clearly recognised. An important characteristic of the economic dynamics of the city is sectoral specialisation within ethnic groups. This was decisively influenced by the way the functions of the city had developed up to the time it was incorporated into Italy. The fascist period brought not only a complete reorganization of the public sector but also the establishment of heavy industries in what remains an unfavourable location. The population, which had reacted 104,000 by 1973, has a 4 to 1 ratio of Italian- to German-speaking inhabitants. Despite difficulties and conflicts of interest the German language group has retained its traditional position in trade, finance and tourism. In this way vital tertiary activities have, in the tradition of spatial location theory, remained within the old city and taken on agglomerative character. Segregation exists not only in different branches of economic activity but also in the localisation of service trades within the urban structure. All aspects of economic life show tendencies to excessive proliferation. Retail trade is most strongly characterised by a social basis of economic marginality. The competitive position of both ethnic groups is embedded in the overall economic and demographic situation of the State. In particular, migration from the old provinces of Italy has been strongly influenced by the state of the labour market inside and outside Italy. Periods of general economic growth lead to a slackening of competition. Assimilation measures become more important. The educational structure also forms an important qualification factor in economic competition.